FORMASI PUBLIC SPHERE DALAM MASYARAKAT TRANSISIONAL (Studi Kasus Penyusunan Peraturan Daerah Nomor 3 Tahun 2007 Tentang Limbah Padat di Kabupaten Luwu Timur, Provinsi Sulawesi Selatan) - Jannus Timbo Halomoan Siahaan (Department of Governmental Science FISIP UNPAD, 2017)
The public sphere popularized by Jurgen Habermas is the result of a review of the reality of 18th century European society. In his work, Habermas mentions that capitalism at that time succeeded in liberating European society from its dependence on the influence of feudalism imposed by the church and monarchy, whose form was a community discussion room aimed at critiquing traditional power (Church and Kingdom). In other words, the power of capitalism has succeeded in creating a space of social debate that was once influenced by feudal power until it switched to a social area free from the domination of feudal power where in that public sphere society has a right in giving criticisms of social problems. If in Europe the development of the public sphere is influenced by the development of capitalism, then what about the implementation of the public sphere in transitional society in Indonesia or especially in the East Luwu community? This paper seeks to explore how the implementation of public space as a concept in transitional society, especially in the East Luwu region in particular related to the process of making a Regional Regulation no. 03 of 2007 on Hazardous Solid Waste. The results of field research indicate that people are still having difficulty in accessing information related to policies related to public life in real terms. At the same time, the government itself also difficulties in distributing information that is actually needed by the community. The government, the DPRD or the people of East Luwu have indeed agreed to provide a discussion space to the public regarding the making of the solid waste management regulation. However, the implementation did not find the appropriate way from the formulation process until the socialization of a local regulation.